THE PROBLEMS OF EVIDENCE ADMISSIBILITY IN THE CRIMINAL PROCEDURE OF THE REPUBLIC OF KAZAKHSTAN - Bersugurova L.Sh.; Dyussembayeva A.S. (Хабаршы. Заң сериясы, 2019)
The article is devoted to the study of theoretical and practical problems of admissibility of evidence in criminal cases in the light of the changes introduced by the criminal procedure legislation to this institution. In the article are analyzed the procedures for resolving questions about the inadmissibility of evidence as evidence in their legal and practical reality. Here we focus on the analysis of the controversial practice of recognizing the inadmissibility of evidence in criminal cases. The material-genesis of the formation of objective criteria for the admissibility of evidence in the criminal process of the Republic of Kazakhstan is analyzed. Admissibility is considered as a mandatory feature of evidence in the criminal process of the Republic of Kazakhstan. It is concluded that the objective criterion for the admissibility of evidence in the criminal process of the Republic of Kazakhstan should be material truth. The article pays attention to the analysis of the concept of the discursiveness of the powers of law enforcement officials to establish the admissibility of evidence at the pretrial stages of criminal proceedings. It is proved that the extended use of the discursive capabilities of the inquiry officer and investigator to determine the admissibility of evidence leads to the uncontrolled making of procedural decisions that do not meet the requirements of justice. Allowed at the stage of pre-investigation procedural violations of procedural legislation have a significant impact on the prospects for judicial consideration of the case.